Church leader's Interpretation of COVID-19 in Nigeria: Science, Conspiracies, and Spiritualization - Nche, George C. (Journal of religion and health, 2024)
The need for governments across the globe to collaborate with religious leaders in the fight against COVID-19 has been emphasized by international organizations including the World Health Organization (WHO). However, there has not been much discernible scholarly effort to know what religious leaders think of COVID-19. The present study, therefore, explored the interpretations church leaders have about COVID-19 in Nigeria. Semi-structured interviews were conducted with eighteen leaders from Catholic, Anglican and Pentecostal churches in Nigeria. Using a thematic analytical approach, the study found that only few church leaders interpreted COVID-19 as a medical problem in line with science (33%). The rest interpreted the virus as a tool of conspiracies/political manoeuvrings (27%) and as a spiritual event (39%). The study discussed the implications of the findings for policy and research as well as how to address some of the harmful interpretations.